Desain dan Implementasi Band Pass Filter Chebyshev dengan M-Derived Section pada Band Frekuensi 88 – 108 MHz - dini novarianti (Jurnal Jaringan Telekomunikasi, 2019)
FM radio broadcasting is a wireless communication system. Transmission in the frequency 88-108 MHz requires a bandpass filter to avoid interference with frequencies adjacent to the radio transmitter. The type of filter that has a fairly good performance is the Chebyshev filter with a fairly high level of steepness. However, to get a high level of steepness, a fairly large element value is required. So, in this study adding the m-derived series to give a steeper filter response without adding more element values.The purpose of this thesis is to determine the effect of adding an m-derived section to the chebyshev bandpass filter. The parameters tested are passband bandwidth, stopband bandwidth, shape factor, insertion loss, roll off, and power attenuation when used on the transmitter.Based on the measurements that have been made, it can be seen that the bandpass filter without m-derived has a maximum insertion loss value of 7 dB and a minimum insertion loss of 9 dB, while the bandpass filter with m-derived is 11 dB and 13. In the bandpass filter without m-derived and m-derived have a passband bandwidth of 27 MHz and 29 MHz and a stopband bandwidth of 70 MHz and 50 MHz. So that the bandpass filter without derived and m-derived has a shape factor value of 2.59 and 1.72. In the implementation using the transmitter, the bandpass filter without m-derived has a power attenuation of 2.53 dB while the m-derived bandpass filter has an attenuation of 1.5 dB.